Comparative Study of Between Nanosecond Leser and Femtosecond Leser: Examining the Effects of Laser Pulse Duration on Nanoparticle Generation in Liquid Environments (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Micro- and Nano-machine researchers were especially interested in producing nanoparticles in liquid environments due to the straightforward method and the direct application of organic solvents with the ultra-short interaction of the laser pulse with materials. Furthermore, laser-produced colloidal nanoparticles are very pure — free of surfactants and reaction products or by products. This chapter examines the duration of the laser pulses in laser material processing of nanosecond, picosecond and femtosecond. Due to the special properties of laser pulse duration, which are short and ultra-short, in material processing, precise material processing and nanoparticles generation in liquid environments become more obvious laser.